Perlindungan Hukum bagi Para Pihak terkait Pemalsuan yang Dilakukan oleh Karyawan Kantor Notaris dalam Pembuatan Akta Otentik - Suminar, Enden; Franciska, Wira; Kadir, Taqiyuddin (Universitas Islam Negeri Alauddin Makassar, 2024)
The phenomenon that occurs is that there are many cases of forgery committed by employees of the Notary office in making authentic deeds that are not in accordance with the procedures in making authentic deeds. Based on this background, there is a formulation of the problem, namely, what are the legal consequences of authentic deeds related to the making of deeds forged by employees of the Notary office? and how is the legal protection for the parties related to the deed forged by the Notary office employee? The theories used are the Theory of Legal Consequences according to Soeroso and the Theory of Legal Protection according to Satjipto Rahardjo. The method used in this study is a type of normative juridical research, namely literature law research or secondary data with primary, secondary and tertiary legal sources. The research approach used is the legal and regulatory approach, the case approach, the analytical approach and the conceptual approach and the technique of collecting legal materials is carried out by identifying and inventorying positive legal rules, literature, books, journals and other sources of legal materials. For legal material analysis techniques, grammatical legal interpretation and systematic legal interpretation are carried out. From the results of the research, it can be concluded that the legal consequences of authentic deeds that contain elements of forgery and in making them violate the provisions of the applicable laws and regulations, then the authentic deed can be submitted for cancellation because it is an action that contains procedural defects, namely the incompetence of the Notary and/or as PPAT to make authentic deeds while legal protection for the parties due to the occurrence of forgery committed by Notary employees, namely the parties can report Notary employees to seek criminal liability Notary employees and Notary civil liability.